Construct validity and internal consistency of the neuropsychiatric inventory – nursing home (NPI-NH) in German nursing homes. (7th January 2016) - Reuther, Sven; Dichter, Martin N.; Bartholomeyczik, Sabine; Nordheim, Johanna; Halek, Margareta
ABSTRACT: Background: The Neuropsychiatric Inventory (NPI) is one of the most popular and frequently used instruments for assessing so-called challenging behavior in individuals with dementia in research practice. However, no information is available regarding the factor structure of the German version of the Neuropsychiatric Inventory – Nursing Home (NPI-NH). The aim of this study was to evaluate the factor structure (an aspect of construct validity) and internal consistency of the NPI-NH for two different stages of dementia severity in a large German nursing home population. Methods: A total of 784 residents with dementia from 40 nursing homes in three studies was included in a secondary data analysis. Principal component analysis (PCA) using an orthogonal rotational procedure (with varimax rotation) was used to evaluate the factor structure of the NPI. Cronbach's α was used to assess the stability of the scale. Results: The factors agitation & restless behavior, psychosis, and mood were identified (with factor loading > 0.4 explaining 50% of the variance). The factors showed a moderate internal consistency of 0.55 and 0.68 (Cronbach's α ). Conclusions: The results show the acceptable factor structure of the NPI for a German population in nursing homes and confirm the results of studies from other countries. The three identified factors appear to be robust over the various stages of dementia severity. The results also support the hypothesis that the NPI-NH can be subdivided into multiple domains.